Non-linear variability in microquasars in relation with the winds from their accretion disks - Janiuk, Agnieszk (2015)
The microquasar IGR J17091-3624, which is the recently discovered analogue of the well known source GRS 1915+105, exhibits quasi-periodic outbursts, with a period of 5-70 seconds, and regular amplitudes, referred to as “heartbeat state”. We argue that these states are plausibly explained by accretion disk instability, driven by the dominant radiation pressure. Using our GLobal Accretion DIsk Simulation hydrodynamical code, we model these outbursts quantitatively. We also find a correlation between the presence of massive outflows launched from the accretion disk and the stabilization of its oscillations. We verify the theoretical predictions with the available timing and spectral observations. Furthermore, we postulate that the underlying non-linear differential equations that govern the evolution of an accretion disk are responsible for the variability pattern of several other microquasars, including XTE J1550-564, GX 339-4, and GRO J1655-40. This is based on the signatures of deterministic chaos in the observed lightcurves of these sources, which we found using the recurrence analysis method. We discuss these results in the frame of the accretion disk instability model.